Isotermas de Adsorção de Diferentes Corantes Têxteis sobre Quitosana - Chaves, J.A.P.; Souza, A.G.; Bezerra, C.W.B.; Silva, H.A.S.; Santana, S.A.A.; Pires Vieira, Adriana; Schultz, M.S. (2008)
Adsorption isotherm of some textile dyes onto chitosan. The biopolymer chitosan was employed as adsorbent material to remove some textile dyes (blue R 160% Rcmazol, ru.bine S-2G Dianix, turquoise G 133% Remazol, red RB gran 133% Remazol and brilliant violet 5R Remawl) from aqueous solutions at pH 6.0. The obtained isothenns pointed out the following adsorption capacity sequence: (mg.g-I ): blue (952.4) > violet (699.3) > red (418.4) > rubine (294.1) > turquoise (245.1). The experimental data for all textile dyes studied showed that the equilibrium isotherms correlated very well with the Langmuir isotherm equation.